2002
DOI: 10.1136/heart.87.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting compensatory vascular remodelling of the carotid artery affected by atherosclerosis

Abstract: Objective: To investigate factors predicting the development of outward remodelling of the carotid artery in patients with atherosclerosis. Design: 130 patients with carotid artery stenosis (15-85% of the vessel diameter) were divided into two groups, based on the presence or absence of outward remodelling of the sclerotic carotid segment on high resolution ultrasonography. Logistic regression analysis was used to evaluate the contribution of haemodynamic, laboratory, and clinical measurements on the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Finally, in the studies of both DRAGER et al [4] and BAGUET et al [3], only OSA patients exhibiting the most severe oxygen desaturation showed carotid hypertrophy. IMT is an established predictor of atherosclerosis [34], but luminal diameter has also been recommended for measurement since there is evidence for an association between increased diameter and the early stages of vascular remodelling [35][36][37]. Moreover, DRAGER et al [3] have used the same parameter in assessing atherosclerosis in OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the studies of both DRAGER et al [4] and BAGUET et al [3], only OSA patients exhibiting the most severe oxygen desaturation showed carotid hypertrophy. IMT is an established predictor of atherosclerosis [34], but luminal diameter has also been recommended for measurement since there is evidence for an association between increased diameter and the early stages of vascular remodelling [35][36][37]. Moreover, DRAGER et al [3] have used the same parameter in assessing atherosclerosis in OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for remodelling are not known although haemodynamic effects may partly explain it. 19 We have shown that atherosclerotic lesions that develop within 12 weeks in rabbit aortae as a result of high-fat diet feeding and balloon injury can be visualised by MRI. There was also a good correlation between aortic lesion (wall) areas measured by MRI and histology.…”
Section: Studymentioning
confidence: 98%
“…However, the mechanisms underlying the transition from expansive remodelling to lumen obstruction still remain unclear. It has been suggested that factors such as smoking, age [5] and fibrocalcific plaque [6] may influence the remodelling process.…”
Section: Introductionmentioning
confidence: 99%